Resistance to Tomato Yellow Leaf Curl Virus in Tomato Germplasm - Yan, Zhe; Pérez-de-Castro, Ana; Díez, Maria J.; Hutton, Samuel F.; Visser, Richard G. F.; Wolters, Anne-Marie A.; Bai, Yuling; Li, Junming (Frontiers in Plant Science, 2018)
Tomato yellow leaf curl virus (TYLCV) is a virus species causing epidemics in tomato (Solanum lycopersicum) worldwide. Many efforts have been focused on identification of resistance sources by screening wild tomato species. In many cases, the accession numbers were either not provided in publications or not provided in a consistent manner, which led to redundant screenings. In the current study, we summarized efforts on the screenings of wild tomato species for TYLCV resistance from various publications. In addition, we screened 708 accessions from 13 wild tomato species using different inoculation assays (i.e. whitefly natural infection and Agrobacterium-mediated inoculation), from which 138 accessions exhibited no TYLCD symptoms. These symptomless accessions include 14 accessions from S. arcanum, 43 from S. chilense, 1 from S. chmielewskii, 28 from S. corneliomulleri, 5 from S. habrochaites, 4 from S. huaylasense, 2 from S. neorickii, 1 from S. pennellii, 39 from S. peruvianum, and 1 from S. pimpinellifolium. Most of the screened S. chilense accessions remained symptomless. Many symptomless accessions were also identified in S. arcanum, S. corneliomulleri, and S. peruvianum. A large number of S. pimpinellifolium accessions were screened. However, almost all of the tested accessions showed TYLCD symptoms. Further, we studied allelic variation of the Ty-1/Ty-3 gene in few S. chilense accessions by applying virus-induced gene silencing and allele mining, leading to identification of a number of allele-specific polymorphisms. Taken together, we present a comprehensive overview on TYLCV resistance and susceptibility in wild tomato germplasm, and demonstrate how to study allelic variants of the cloned Ty-genes in TYLCV-resistant accessions.